Region As a Factor Influencing Innovativeness of Enterprises: On the Example of The Zachodniopomorskie Province - Piotr ŁADNY (Communications of International Proceedings, 2021)
Innovation policy in Poland has undergone dynamic changes in recent years, both in the systemic sphere and that related to the economic effectiveness of the proposed solutions - it has been evolving from a central model towards a model based on the introduction of effective mechanisms of public expenditure control, the implementation of new functions by the public sector and the development of innovation at the local level. In this context, the regional level becomes one of the primary areas of interest for innovation policy, and the region with its specific characteristics is the target area for support. The aim of the article is to assess the effects of actions taken in 2005-2020 related to the creation of regional innovation strategies on the growth of innovation potential of Polish regions on the example of the Zachodniopomorskie Province. On the basis of changes in the innovative potential of the region carried out on the basis of the regional innovation index, it was indicated that the development of innovativeness at the regional level requires a wide range of actions enabling effective implementation of the provisions of the strategy and including the creation of a well thought-out regulatory and financial system of innovation support with particular consideration for the challenges related to the practical application of new solutions and the results of research and development works in the public sector and in business. The research method adopted by the author is secondary research, based on an analysis of the literature and the results of studies on innovation in regional terms and the evaluation of the level of innovation of Polish regions on the example of the Zachodniopomorskie Province.
Keywords: Region; Innovation; Zachodniopomorskie Province